1995
DOI: 10.1111/j.1439-0426.1995.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

A short note on the effects of vitamin A hypervitaminosis and hypovitaminosis on health and growth of Tilapia nilotica (Oreochromis niloticus)

Abstract: A total of 120 Tilapia nilotica fingerlings were fed diets supplemented with 0, 5000, 10 000 and 40 000 IU vitamin A k -' diet, respectively, at a rate of 3% of body weight for 18 weeks. The Vitamin A unsupplementef grou developed severe signs of vitamin deficiencies (restlessness, abnormal movement, blindness, exop%thalmia, haemorrhages of eyes, fins and skin, pot-belly syndrome, reduced mucous secretion). Growth and feed consumption were severely depressed, and the mortality rate amounted to 48%. An addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
56
4
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 4 publications
13
56
4
6
Order By: Relevance
“…Hu et al (2006) reported that hybrid tilapia fed diets supplemented with 50,000 IU vitamin A kg -1 present better weight gain (601%) and better feed conversion ratio (1.00). Saleh et al (1995) also observed that Nile tilapia juveniles fed diets supplemented with 5,000 IU vitamin A kg -1 presented better weight gain (23.9 g), better feed consumption rate (60.2 g), and better feed SR = sex-reverted; NSR = non sex-reverted conversion ratio (2.5), than fish fed diets containing 0, 10,000 or 40,000 IU vitamin A kg -1 . Mohamed et al (2003) observed that diets supplemented with 3,764 mg vitamin A kg -1 for greasy grouper led to a better weight gain (420.94%), better feed conversion ratio (1.42) and better protein efficiency ratio (2.08).…”
Section: Growth Parametersmentioning
confidence: 73%
See 2 more Smart Citations
“…Hu et al (2006) reported that hybrid tilapia fed diets supplemented with 50,000 IU vitamin A kg -1 present better weight gain (601%) and better feed conversion ratio (1.00). Saleh et al (1995) also observed that Nile tilapia juveniles fed diets supplemented with 5,000 IU vitamin A kg -1 presented better weight gain (23.9 g), better feed consumption rate (60.2 g), and better feed SR = sex-reverted; NSR = non sex-reverted conversion ratio (2.5), than fish fed diets containing 0, 10,000 or 40,000 IU vitamin A kg -1 . Mohamed et al (2003) observed that diets supplemented with 3,764 mg vitamin A kg -1 for greasy grouper led to a better weight gain (420.94%), better feed conversion ratio (1.42) and better protein efficiency ratio (2.08).…”
Section: Growth Parametersmentioning
confidence: 73%
“…Vitamin A deficiency signs in O. niloticus include: abnormal swimming behavior; internal hemorrhages; protruded, blind eyes; anemia; hemorrhage in the base of fins and in the skin (Saleh et al, 1995). In advanced deficiency condition Saleh et al (1991) also observed widespread depigmentation and edemas in the abdomen, sometimes associated with ascites; reduction of mucus secretion and dry, hard mucous tissue.…”
Section: Deficiency Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were many VA deficiency symptoms reported in fish, such as depressed feed consumption (Saleh et al 1995), hemorrhages in eyes, fins and skin (Moren et al 2004), cataract (Moren et al 2004, Hemre et al 2004, photophobia (Hu et al 2006), bone deformities (Yang et al 2008) and lack of pelvic fins (Mazurais et al 2009). In this study, vertebral deformities were visibly observed in grass carp, and the incidence of this deformity in 68 IU/kg group was much higher than that in 328 IU/kg group, which may suggest the indispensability of VA to the skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A (VA) shares a variety of biochemical functions, including maintaining normal vision, controlling the differentiation and proliferation of cells (Moren et al, 2004;Hemre et al, 2004), participating in mucus production and bone growth (Saleh et al, 1995), regulation of glucose concentrations and lipid metabolism of the whole body (Mohamed et al, 2003;Hernandez et al, 2005), affecting fish immune responses (Rhee et al, 2012;Furuita et al,2001; Thompson et al, 1995). Stunted growth and development of fish have been reported when insufficient or excessive VA intake occured, especially in juvenile fish (Rønnestad et al, 1998).…”
Section: Introductionmentioning
confidence: 99%